2021
DOI: 10.1007/s40687-021-00265-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectral methods for nonlinear functionals and functional differential equations

Abstract: We present a rigorous convergence analysis for cylindrical approximations of nonlinear functionals, functional derivatives, and functional differential equations (FDEs). The purpose of this analysis is twofold: First, we prove that continuous nonlinear functionals, functional derivatives, and FDEs can be approximated uniformly on any compact subset of a real Banach space admitting a basis by high-dimensional multivariate functions and high-dimensional partial differential equations (PDEs), respectively. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…where F [n] is some functional of n [24,23] while and the second term on the right had side represents the interaction of electrons with the external potential created from the nuclei. The Hohenberg-Kohn theorems showed that the functional F [n] exists.…”
Section: Brief Review Of Density Functional Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…where F [n] is some functional of n [24,23] while and the second term on the right had side represents the interaction of electrons with the external potential created from the nuclei. The Hohenberg-Kohn theorems showed that the functional F [n] exists.…”
Section: Brief Review Of Density Functional Theorymentioning
confidence: 99%
“…The significant improvement in accuracy given by GGA functionals led to the wider adoption of density functional theory across chemistry and material science [13]. The exchange-correlation potential V XC in ( 7) is the first-order functional derivative [24] of…”
Section: Brief Review Of Density Functional Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Computing the solution of high-dimensional partial differential equations (PDEs) has become central to many new areas of application such as optimal mass transport [13,48], random dynamical systems [21,46,47], mean field optimal control [11,38], and functional-differential equations [45,44]. Classical numerical methods based on full tensor product discretizations are not viable in practice, due to the exponential growth of the degrees of freedom with the dimension.…”
Section: Introductionmentioning
confidence: 99%